Diagnosis “Autism” – from Kanner and Asperger to DSM-5 - Achkova, Meglena; Manolova, Harieta (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
The authors make a synthesized overview of the evolution of the understanding of autism in historical context and a critical analysis of the development of diagnostic criteria in the spirit of the Diagnostic and Statistical Manual (DSM). Based on personal research and extensive clinical experience they put forward a number of debatable issues and own views about the nature of autistic disorder by outlining the trends and directions for future research. Discussed is the issue of "core" and "additional" symptoms of autism and the need for comparison of categorical and dimensional data when constructing empirical studies for the autistic population. The article contains reflections on the underlying impairment which, according to the authors, is a disturbance in the processing and integration of the incoming information, especially at the level of filtration of significant and insignificant stimuli and their linking into a mental sequence appearing at different levels and with varying degree of severity. Noted is the importance of the detailed assessment of mental functioning for early diagnosis and individualized targeting of the therapeutic efforts. In this regard is emphasized the need to search for a new paradigm in the methodology of future research on autism that would make possible the comparison of interdisciplinary results and identification of connections between the relevant scientific achievements. Thus it will be possible to identify trends that will bring us closer to revealing the etiology, perhaps will have an impact on the criteria for diagnosis and on the overall construction of future therapeutic strategies.